Komnas HAM, Investigating Serious Human Rights Violations - Amiruddin Amiruddin (Jember University Press, 2021)
This paper reviews the dynamics and challenges of the investigation conducted by Komnas HAM in accordance with Law No. 26/2000 of the Human Rights Court. In addition, this paper also explains the dynamics between Komnas HAM and the Attorney General as an investigator in Law No.26/2000. A critical related issue is the provision of the authority to investigate the National Human Rights Commission and the Attorney General's Office, which have been a serious obstacle to resolving gross human rights violations in Indonesia. This article also provides an analysis of the likely challenges faced by Komnas HAM in future investigations.